2016
DOI: 10.1177/0731684416635757
|View full text |Cite
|
Sign up to set email alerts
|

Vibration and stability of laminated composite orthogrid plates

Abstract: Generally, a grid layer is used as an orthotropic layer to reinforce plates and shells or as an independent structural element. The proposed laminated grid plate is composed of different grid layers with different orientations. Consequently, the grid layers with different fibers, patterns and orientations can be used, resulting in laminates with enhanced stiffness and coupling effects. In the present study, to investigate the efficiency of the laminated grids, the vibration and buckling responses of a conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Where [K] and [K G ] are the elastic and geometric stiffness matrices, andd is the vector of coefficients (W mn , R mn and S mn ) that can be presented as below 18 :…”
Section: Constitutive Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Where [K] and [K G ] are the elastic and geometric stiffness matrices, andd is the vector of coefficients (W mn , R mn and S mn ) that can be presented as below 18 :…”
Section: Constitutive Equationsmentioning
confidence: 99%
“…Achieving the λ from Equation (20), the buckling loads can be calculated. To calculate the free vibration frequencies, the energy function of the plate's vibration based on FSDT can be presented as 18 :…”
Section: Constitutive Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They investigated lamination effects on stiffness and mechanical behavior of grid structures. Ehsani et al [7,8] studied the influence of the stacking sequence and pattern composition on buckling load of laminated composite grid plates and also conducted studies on the buckling load and natural vibration of laminated orthogrid plates. Their results showed that, there are proper stacking sequences, which considerably improves the mechanical behaviors of the grid structures.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the many studies on different types of grid structures there have been rare investigations on the applications of laminated grid structures. Similar to a laminated composite, laminated grid is composed of different grid layers with different orientations, which can improve the stiffness and coupling effects of conventional grids [8]. Tailored stiffness of a structure is achieved by employing full anisotropic properties of a laminated grid compare to orthotropic properties with at most in plane anisotropic of a corresponding conventional grid [6].…”
Section: Introductionmentioning
confidence: 99%